Lipocalin-2 participates in sepsis-induced myocardial injury by mediating lipid accumulation and mitochondrial dysfunction - Liu, Weizhuo; Guo, Xiaoyu; Jin, Lei; Hong, Ting; Zhang, Qianyun; Su, Fan; Shen, Yi; Li, Saiqi; He, Bin (Frontiers in Cardiovascular Medicine, 2022)
Background Sepsis-induced cardiomyopathy (SIC) is one major cause of death for sepsis but lacks timely diagnosis and specific treatment due to unclear mechanisms. Lipocalin-2 (LCN-2) is a key regulator of lipid metabolism which has been recently proved closely related to sepsis, however, the relationship between LCN-2 and septic myocardial injury remains unknown. We aim to explore the role of LCN-2 in the pathological progress of SIC based on clinical and laboratory evidence. Methods Consecutive patients admitted to the intensive care unit (ICU) from August 2021 to April 2022 fulfilling the criteria of severe sepsis were included. The level of LCN-2 in plasma was assayed and analyzed with clinical characteristics. Biostatistical analysis was performed for further identification and pathway enrichment. Mouse model for SIC was thereafter established, in which plasma and tissue LCN-2 levels were tested. RNA sequencing was used for verification and to reveal the possible mechanism. Mitochondrial function and intracellular lipid levels were assayed to further assess the biological effects of targeting LCN-2 in cardiomyocytes with small interference RNAs (siRNAs). Results The level of LCN-2 in plasma was markedly higher in patients with severe sepsis and was associated with higher cardiac biomarkers and lower LVEF. In the in vivo experiment, circulating LCN-2 from plasma was found to increase in SIC mice. A higher level of LCN-2 transcription in myocardial tissue was also found in SIC and showed a clear time relationship. RNA sequencing analysis showed the level of LCN-2 was associated with several gene-sets relevant to mitochondrial function and lipid metabolism-associated pathways. The suppression of LCN-2 protected mitochondrial morphology and limited the production of ROS, as well as restored the mitochondrial membrane potential damaged by LPS. Neutral lipid staining showed prominent lipid accumulation in LPS group, which was alleviated by the treatment of siLCN2. Conclusions The level of LCN-2 is significantly increased in SIC at both circulating and tissue levels, which is correlated with the severity of myocardial injury indicators, and may work as an early and great predictor of SIC. LCN-2 probably participates in the process of septic myocardial injury through mediating lipid accumulation and affecting mitochondrial function.